The Impact of Multimodal Discourse on Iraqi EFL Learners' Writing Skills - et. al., Mohammad Kiani Harchegani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study was conducted to investigate the impact of multimodal discourse on Iraqi EFL learners' writing skills. To achieve the goal, a group including 40 Iraqi EFL learners participated in the free paragraph writing course based on their scores in a Placement Test. Selected participants were randomly assigned to control (N=20) and experimental (N=20) groups. Prior to the start of the course, both groups were given the pretest (writing test). The experimental group was exposed to the treatment (multimodal use of discourse, e.g. video and picture based on Halliday’s social semiotics approach) and the control one did not receive any treatment. Having accomplished the experiment, participants of the two groups completed two writing tasks as the posttest. Results of t-test indicate significant outperformance of the experimental group over the control one